Winners and losers in subarctic moth communities in a changing climate: Marine regime shifts as predictors for terrestrial insect biomass - Fält‐Nardmann, Julia J. J.; Rousi, Heta E. J.; Juutilainen, Ilmari; Andersson, Tommi; Marjamäki, Betty; Itämies, Juhani; Niemelä, Pekka; Hänninen, Jari (Wiley, 2026)
Understanding the role of climate change in the globally reported declines of insect populations is difficult due to complex interactions between climate and other drivers, such as agricultural practices and changes in land use practices.
We focused on subarctic moth communities in northernmost Finland, a region with significant climatic changes and minimal human impact. We use moth species abundance data from 45 years of light-trap monitoring at the Kevo Subarctic Research Institute.
TRIM analyses showed a significant positive trend in total moth biomass between 1972 and 2017.
There were large differences in biomass trends between different groups based on life-history traits.
Seven trait-based groups had significant positive population trends: species pupating early in the season, overwintering as eggs, feeding as larvae on live vascular plants, feeding on both herbaceous and woody plants, species with larvae chewing freely on leaves and those with leaf-rolling larvae, as well as generalists feeding on at least three plant genera.
Moths overwintering as larvae, species feeding only on herbaceous plants and specialists feeding on only one plant genus had negative trends.
Five groups had no significant trends.
Linear mixed models revealed significant correlations between regime shifts in the Baltic Sea and biomass in five moth groups. Temperature and degree-day variables were also important. A negative relation between a positive NAO (North Atlantic Oscillation) index in spring and moth biomass was implied.
Our results suggest that large-scale oceanic climate patterns, such as regime shifts and the NAO, can be useful proxies for predicting the effects of complex climatic phenomena on terrestrial ecosystems.